In Situ Synthesis of Surface-Mounted Novel Nickel(II) Trimer-Based MOF on Nickel Oxide Hydroxide Heterostructures for Enhanced Methanol Electro-Oxidation - Sun, Ya-Ya; Wang, Yan-Jiang; Pi, Qiu; Wu, Ya-Pan; Wu, Xue-Qian; Li, Shuang; Lan, Ya-Qian; Zhang, Qichun; Li, Dong-Sheng (Frontiers in Chemistry, 2021)
Engineering the heterogeneous interface fusing MOFs and inorganic active component is an effective strategy to improve the electrochemical performance. Herein, we report a new Ni3-based MOF (denoted as CTGU-24) with an infrequent two-fold interpenetrating 3D (3,8)-connected network constructed from Ni(II) trimer and mixed tripodal tectonics for the electrocatalytic methanol oxidation reaction (MOR). In order to improve its stability and activities, the heterogeneous hybrid CTGU-24@NiOOH has been fabricated successfully via the first preparation of the NiOOH nanosphere and then in situ formation of CTGU-24 decorated on the NiOOH surface. Moreover, the integration of CTGU-24@NiOOH and different additives [acetylene black (AB) and ketjen black (KB)], resulting in the optimized hybrid sample AB&CTGU-24@NiOOH (4:4). It attains better MOR performance with an area-specific peak current density of 34.53 mA·cm−2 than pure CTGU-24 (14.99 mA·cm−2) and improved durability in an alkali medium. The new findings indicate that the CTGU-24@NiOOH heterostructure formed in situ and the integration of moderate additives are critical to optimizing and improving electrocatalytic activity of pure MOF crystalline material.